Artery of percheron infarction: case reports and literature review - Kulshreshtha, Dinkar; Maurya, Pradeep K.; Chhirolya, Rohit; Singh, Ajai K.; Thacker, Anup K.; Kulshreshtha, Dinkar (International Journal of Research in Medical Sciences, 2017)
The artery of Percheron is a rare anatomic variant supplying the thalamus and the rostral midbrain. Infarct in this territory results in a wide array of neurological signs and symptoms causing diagnostic dilemma and management issues. We describe the clinical presentations in three cases admitted and evaluated for neurological symptoms and diagnosed as artery of percheron infarct after brain imaging. In one patient, the etiology turned out to be infective while the other two patients had cerebrovascular accident secondary to dilated cardiomyopathy and hyper homcystinimea respectively. Artery of percheron infarction is a rare entity and should be considered in patients with altered sensorium and behavioral manifestations with associated eye abnormalities. MRI brain is the investigation of choice to detect this rare variant of thalamic circulation.